2020
DOI: 10.3389/fphys.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Activates the Antioxidant Machinery and Inhibits the Inflammatory and Apoptotic Cascades Against Lead Acetate-Induced Renal Injury in Rats

Abstract: The kidney is among the metabolic organs most susceptible to injury, particularly following exposure to xenobiotics and heavy metals. We aimed to explore the potential protective impacts of coenzyme Q10 (CoQ10) on lead acetate (PbAc)-induced nephrotoxicity in rats. Four experimental groups (n = 7) were applied as follows: control group, CoQ10 alone (10 mg/kg), PbAc alone (20 mg/kg), and PbAc with CoQ10. Exposure to PbAc led to the accumulation of Pb in the kidney and increased urea and creatinine serum levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…Lead has a high affinity for thiol groups or metal cofactors in enzymatic and non‐enzymatic antioxidants and molecules, the binding of which results in a decline in antioxidant enzyme activities, including SOD, CAT, GPx, and GR activities (Baty et al., 2020). Our experimental findings are in accordance with those of AL‐Megrin, Soliman, et al (2020), who reported a prominent elevation in hepatic MDA levels and a marked depletion in enzymatic and non‐enzymatic antioxidants and molecules. SOD, CAT, and GPx form the first line of defense against ROS, and decrease in their activities contributes to oxidative stress in tissues.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lead has a high affinity for thiol groups or metal cofactors in enzymatic and non‐enzymatic antioxidants and molecules, the binding of which results in a decline in antioxidant enzyme activities, including SOD, CAT, GPx, and GR activities (Baty et al., 2020). Our experimental findings are in accordance with those of AL‐Megrin, Soliman, et al (2020), who reported a prominent elevation in hepatic MDA levels and a marked depletion in enzymatic and non‐enzymatic antioxidants and molecules. SOD, CAT, and GPx form the first line of defense against ROS, and decrease in their activities contributes to oxidative stress in tissues.…”
Section: Discussionsupporting
confidence: 93%
“…CAT and SOD are important antioxidant agent catalysts that play critical roles in the removal of superoxide from the natural framework. Pb can supplant zinc and other significant cofactor metals, leading to the loss of a protective antioxidant response in addition to lowering GSH activity (AL‐Megrin, Soliman, et al, 2020). Curiously, MOE treatment forestalls oxidative stress, indicating its remarkable protective effect in cortical tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 To date, several endogenous free radical scavengers (including enzymatic factors such as catalase, superoxide dismutase (SOD), and selenium and / or non-selenium-dependent glutathione peroxidase (GPx) and nonenzymatic scavengers, such as glutathione (GSH); bilirubin; albumin; vitamins A, E, and C; selenium, uric acid, and coenzyme Q-10, have been identified in both the membranes and cytoplasm of cells. 8 Arsenic induces oxidative pressure through excessive overproduction of reactive oxygen and nitrogen species (ROS/RNS), depletion of the antioxidant capacity of cells, 5 and suppression of DNA repair mechanisms. 2 Arsenic also depletes the cellular concentrations of both enzymatic and nonenzymatic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In mitochondria, CoQ10 plays a critical role in producing adenosine triphosphate (ATP) via the oxidative phosphorylation pathway [9,10]. Recently, CoQ10 has been reported to have anti-inflammatory functions and exhibit therapeutic effects for immune disorders [11,12]. Some studies have demonstrated therapeutic effects of CoQ10 against RA through the regulation of immune process factors such as tumor necrosis factor (TNF)-α and IL-6 [13,14].…”
mentioning
confidence: 99%